Analysis of Knitting Industry Issues in Bandung - Setijadi (International Journal of Psychosocial Rehabilitation, 2020)
The industry sector of Textile and Textile Products (in Indonesia Tekstil dan Produk Tekstil/TPT) is a manufacturing sector that contributes greatly to Indonesia's Gross Domestic Product (GDP). Some of the entrepreneurs in this sector come from small and medium-sized enterprises (SMEs). The competitiveness in the TPT sector, including the knitting industry, is relatively low. The purpose of this study is to analyze the issues faced by SMEs in the knitting industry in Bandung and to provide recommendations as solutions to the issues. The research is conducted by using the Input-Process-Output-Outcome-Benefit/Impact approach and the value chain analysis. The results of the study suggest that the competitiveness issue in the knitting industry commonly involves various problems of machine and costs of energy, labor, raw materials, market absorption and competition, information, and government/regulatory support. Solutions recommended from this research are related to machining, enhancing human resource competencies, consolidating the sourcing process, developing a shared marketplace, developing a marketplace portal, developing information systems, socializing regulations, collaborating with educational and training institutions, and revitalizing functions and fostering cooperatives.